Oral history and education : theories, dilemmas, and practices - Llewellyn, Kristina R. 1976- Herausgeber; Ng-A-Fook, Nicholas Herausgeber (Palgrave studies in oral history, 2017)
"This book considers if and how oral history is 'best practice' for education. International scholars, practitioners, and teachers consider conceptual approaches, methodological limitations, and pedagogical possibilities of oral history education. These experts ask if and how oral history enables students to democratize history; provides students with a lens for understanding nation-states' development; and supports historical thinking skills in the classrooms. This book provides the first comprehensive assessment of oral history education - inclusive of oral tradition, digital storytelling, family histories, and testimony - within the context of 21st century schooling. By addressing the significance of oral history for education, this book seeks to expand education's capacity for teaching and learning about the past."--Back cover